Ion dynamics and electrical transport in lanthanum silicate apatite (La9.67Si6O26.5) - Yadav A.; Verma O.N.; Pandey R.; Jha N.; Singh P. (My University, 2025)
Lanthanum silicate apatite, La9.67Si6O26.5, LSO, was formed using a solid-state reaction process. X-ray diffraction measurements of the synthesized composition were carried out for structural analysis. Sintering of the pelletized samples was done at 1400 °C for 6 h to obtain the maximum density. Conductivity spectroscopic techniques is used to explore the electrical transport behaviour of the silver-coated pelletized LSO sample. The conductivity spectra of LSO sample were described using Jonscher's power law in the frequency range of 20 Hz to 1 MHz at different temperature. Charge carrier's concentration, exponent factor, dc conductivity and hopping frequency were extracted from the Jonscher’s power law fitting of conducting profile. Power law exponent value and ion migration reaction coordinate indicate predominant one-dimensional migration of oxide ions through interstitials sites. According to the ion migration study, the O4 ions migrate along the c-axis by a deficiency drive with a direct linear path, while the O3 ions migrate orthogonal to the c-axis via an interstitial mode. The associated activation energy value indicates that charge carrier mobility is the primary determinant of ionic conductivity. Obtained value of electrical conductivity suggests that it can be employed as solid electrolyte in solid oxide fuel cells. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.